Antioxidant activity of xylooligosaccharides produced from glucuronoxylan by Xyn10A and Xyn30D xylanases and eucalyptus autohydrolysates. (15th August 2018) - Valls, Cristina; Pastor, F.I. Javier; Vidal, Teresa; Roncero, M. Blanca; Díaz, Pilar; Martínez, Josefina; Valenzuela, Susana V.
Graphical abstract: Highlights: Neutral and/or acidic XOS were obtained depending on the GH family of xylanase used. XOS produced from glucuronoxylans have high antioxidant activity enhanced by the MeGlcA ramifications. Antioxidant power of XOS depends on the degree of polymerisation and substrate used. High antioxidant activity was found on the eucalyptus autohydrolysate. ABTS method is more sensitive method for the XOS antioxidant activity than DPPH. Abstract: Antioxidant activity of xylooligosaccharides (XOS) released from beechwood and birchwood glucuronoxylans by two different xylanases, one from family GH10 (Xyn10A) and another from family GH30 (Xyn30D) was examined. The ABTS (2, 2′-Azino-bis(3-ethylbenzothiazoline-6-sulfonic acid)) method was used, since it resulted more accurate for the antioxidant activity determination of XOS. Thin layer chromatography and MALDI-TOF MS analysis showed that Xyn10A produced a mixture of neutral and acidic XOS whereas the XOS produced by Xyn30D were all acidic, containing a methylglucuronic acid (MeGlcA) ramification. These acidic XOS, MeGlcA substituted, showed a strongly higher antioxidant activity than the XOS produced by Xyn10A (80% vs. 10% respectively, at 200 μg mL −1 ). Moreover, the antioxidant activity increased with the degree of polymerization of XOS, and depended on the xylan substrate used. The antioxidant capacity of eucalyptus autohydrolysates after xylanase treatment was also analysed, showing a decrease of their antioxidant activity simultaneous with the decrease in XOS length.